Morphometric features of asterion in adult human skulls - Deepak, Seema; KR, Dakshayani (International Journal of Research in Medical Sciences, 2017)
Background: Asterion is the meeting point of temporal, occipital and parietal bones on the posterolateral surface of skull and surgically an important point of reference for approaching the posterior cranial fossa structures. However surgeons have been skeptical about its reliability due to population based differences in its morphology, distance with other external landmarks and also to sigmoid and transverse sinuses. Methods: In this study 50 (27 male & 23 female) adult skulls were investigated to determine the type of asterion, its distance from important bony landmarks and also the nearby venous sinuses were measured. Results: Our study revealed that type II (absence of sutural bones) was commoner than type I (presence of sutural bones) asterion. The asterion was 4.82 ± 0.58 cm from tip of the mastoid process on the right side and 4.70 ± 0.70 cm on the left. It was greater in males than in females, p value being statistically significant (P = 0.00 & P = 0.02 for right & left sides respectively). The distance of asterion from supramastoid crest was 4.22 ± 0.73 cm on the right and 4.23+/-0.58 cm on the left. The distance in males was more than in females. The P value 0.00 was statistically significant on the right side. Regarding the position of the asterion in relation to transverse sinus, it was on the transverse sinus in 62% cases, below it in 32% and above in 6%. Conclusions: The data obtained shows that the asterion is located either at the level or below the level of the transverse sinus in majority of the cases. This information is useful to neurosurgeons to reduce the risk during posterior cranial fossa surgeries. This work will also be useful to anthropologists, forensic science experts for determination of sex of the skull along with other parameters.